Experimental Characterization of Dielectric Properties in Fluid Saturated Artificial Shales - Roman Beloborodov; Marina Pervukhina; Tongcheng Han; Matthew Josh (Geofluids)
High dielectric contrast between water and hydrocarbons provides a useful method for distinguishing between producible layers of reservoir rocks and surrounding media. Dielectric response at high frequencies is related to the moisture content of rocks. Correlations between the dielectric permittivity and specific surface area can be used for the estimation of elastic and geomechanical properties of rocks. Knowledge of dielectric loss-factor and relaxation frequency in shales is critical for the design of techniques for effective hydrocarbon extraction and production from unconventional reservoirs. Although applicability of dielectric measurements is intriguing, the data interpretation is very challenging due to many factors influencing the dielectric response. For instance, dielectric permittivity is determined by mineralogical composition of solid fraction, volumetric content and composition of saturating fluid, rock microstructure and geometrical features of its solid components and pore space, temperature, and pressure. In this experimental study, we investigate the frequency dependent dielectric properties of artificial shale rocks prepared from silt-clay mixtures via mechanical compaction. Samples are prepared with various clay contents and pore fluids of different salinity and cation compositions. Measurements of dielectric properties are conducted in two orientations to investigate the dielectric anisotropy as the samples acquire strongly oriented microstructures during the compaction process.